Sensing Platform Based on Gold Nanoclusters and Nanoporous Anodic Alumina for Preeclampsia Detection - Josep Maria Cantons; Akash Bachhuka; Lluis F. Marsal (Biosensors, 2024)
Preeclampsia is a pregnancy-specific hypertensive syndrome recognized as the leading cause of maternal and fetal morbidity worldwide. Early diagnosis is crucial for mitigating its adverse effects, and recent investigations have identified endoglin as a potential biomarker for this purpose. Here, we present the development of a hybrid biosensor platform for the ultrasensitive detection of endoglin, aimed at enabling the early diagnosis of preeclampsia. This platform integrates the high surface area properties of nanoporous anodic alumina (NAA) with the unique optical characteristics of gold nanoclusters (AuNCs) to achieve enhanced detection capabilities. The NAA surface functionalized to promote attachment of AuNCs, which then was functionalized with specific antibodies to confer selectivity towards endoglin. Photoluminescence (PL) analysis of the biosensor demonstrated a linear detection range of 10–50 ng/mL, with a detection limit of 5.4 ng/mL and a sensitivity of 0.004 a.u./(ng/mL). This proof-of-concept study suggests that the NAA-AuNCs-based biosensing platform holds significant potential for the development of ultrasensitive, portable, and cost-effective diagnostic tools for preeclampsia, offering a promising avenue for advancing prenatal care.